Prevalence and predictors of depression in community-dwelling elderly in rural Haryana, India - Manju Pilania; Mohan Bairwa; Hitesh Khurana; Neelam Kumar (Wolters Kluwer Medknow Publications, 2017)
Background: Depression in the elderly has been emerged as a serious public health challenge in the developing countries. Elderly population with depression is on rise in India, but is not adequately addressed. This study was planned to ascertain the prevalence of depression among elderly in a rural population of Haryana and assess its socio-demographic correlates. Methods: This study was a community based, cross sectional study, which was conducted in Community Health Centre (CHC), Chiri of Rohtak district (Haryana, India). Of total 124 Anganwadi centres in study area, 10 were randomly selected. A total 500 elderly persons aged 60 years and above were randomly screened for depression. Long form of Geriatric Depression Scale (GDS- 30) was used with cut off score at 22. The Pearson's Chi-squared test, student's t test, and multiple logistic regression were used to assess the association of depression in the elderly with its risk factors. Result: In our study, the prevalence of depression in the elderly was 14.4% (95% CI: 11.6- 17.8). Mean age of study population was 68.5 ± 7.7 years. Depression in the elderly had significant association with female gender [OR=2.7 (95% CI 1.4- 5.0)], not being consulted for major decisions [OR=2.7 (95% CI 1.5- 4.7)], presence of any chronic morbidity [OR=2.4 (95% CI 1.3- 4.5)], spending day without doing any activity, work or hobby [OR=3.8 (2.1- 7.1)], and death of any close relative in the last 1 year [OR=2 (1.1- 3.7)] after adjustment of various factors. Conclusion: Our study revealed that the prevalence of depression in the elderly was 14.4% in a rural community of north India.